Immune cell infiltrates in peritoneal metastases from colorectal cancer - Sundström, Patrik; Hogg, Stephen; Quiding Järbrink, Marianne; Bexe Lindskog, Elinor (Frontiers in Immunology, 2024)
The presence of peritoneal metastases (PMs) in patients with colorectal cancer (CRC) confers a poor prognosis and only a minority of patients will benefit from the available treatment options. In primary CRC tumors, it is well established that a high infiltration of CD8 + effector T cells correlates to a favorable patient outcome. In contrast, the immune response induced in PMs from CRC and how it relates to patient survival is still unknown. In this study, we characterized the immune infiltrates and the distribution of immune checkpoint receptors on T cells from PMs from CRC, in order to evaluate the potential benefit of checkpoint blockade immunotherapy for this patient group.Methods: Surgically resected PM tissue from CRC patients (n=22) and synchronous primary tumors (n=8) were processed fresh to single cell suspensions using enzymatic digestion. Surface markers and cytokine production were analyzed using flow cytometry.Results: T cells dominated the leukocyte infiltrate in the PM specimens analyzed, followed by monocytes and B cells. Comparing two different PMs from the same patient usually showed a similar distribution of immune cells in both samples. The T cell infiltrate was characterized by an activated phenotype and markers of exhaustion were enriched compared with matched circulating T cells, in particular the checkpoint receptors PD-1 and TIGIT. In functional assays most cytotoxic and helper T cells produced INF- and TNF following polyclonal stimulation, while few produced IL-17, indicating a dominance of Th1-type responses in the microenvironment of PMs. Conclusions: Immune cells were present in all PMs from CRC examined. Although infiltrating T cells express markers of exhaustion, they produce Th1-type cytokines when stimulated. These results indicate the possibility to augment tumor-specific immune responses within PMs using checkpoint blockade inhibitors.